Features of use of prepared medicinal forms of insulin in diabetes - Mamonov, S.V.; Reshetnyak, L.R. (Problems of Environmental Biotechnology, 2023)
Diabetes mellitus, which is the third most common disease in the world, requires the development of affordable domestic recombinant insulin. Insulin plays a key role in ensuring normal glucose metabolism in the body. Long-acting and short-acting insulin are used to mimic physiological insulin secretion and control blood glucose levels. Long-acting insulin is injected into the thigh, while short-acting insulin is injected into the abdomen. Ultra-short-acting drugs begin to act quickly and have a short time of elimination from the body. Insulin glargine, a representative of long-acting insulin, is distinguished by a constant rate of release and the absence of hypoglycemia. There are also combined insulins for the treatment of type 2 diabetes that combine long-acting and short-acting insulins in one drug, facilitating convenient administration.